(untitled) (Journal of Misan Researches, 2020)
Given the tremendous scientific and technical development in all fields, especially the field of education, and the importance of the subject of history and its relationship to other sciences and technology, it has led to a massive accumulation of information and facts, so education has become very important, especially in teaching new models by teachers, an important matter which is one of the educational pillars that education seeks to achieve Which prompted many educators and psychologists to design many educational models in an attempt to facilitate their education for students The aim of the current research is to know the effect of the Karen model on the development of inferential thinking among students of the second intermediate class in the subject of Arab and Islamic history through testing the following zero hypotheses: - Not sure. For the purpose of achieving the research goal, the researcher derived the following zero hypotheses: A -. (There are no statistically significant differences at the level (0.05) between the mean scores of the experimental group that are studied by the Karen model in the inferential thinking test before and after the experiment. B- (There are no statistically significant differences at the level (0,05) between the mean scores of the control group that is studying the subject of Arab Islamic history using the usual method in the inferential thinking test before and after the experiment) C-There are no statistically significant differences at the level of 0.05 between the mean scores of the experimental group that studies the subject of Arab Islamic history according to the Karen model, and the mean of the score of the control group that studies the subject itself in the usual way in the test of inferential thinking after applying the experiment The current research was limited to the second average female students, and the sample reached 42 students in secondary and intermediate schools affiliated to the General Directorate of Education in Baghdad, the second Rusafa / for the academic year 2013-2014 and for the fourth and fifth semesters of the book of Arab Islamic history. I used experimental design with partial control of the two research groups (experimental and control) with the post test, intentionally to apply the experiment and after that the two groups were equal in variables for example (intelligence, previous knowledge, previous academic achievement in the subject of history, time age calculated by months, academic achievement For the father, the academic achievement of the mother) The experimental group was studied according to the Karen model while the group studied the officer according to the usual method of teaching, and the researcher will teach the two groups themselves. The researcher used the appropriate statistical means to achieve the objectives of her research (such as persistence, the difficulty equation and the discriminatory strength of the paragraphs). As for the most important results of the current research, there was a significant difference between the mean levels of achievement of the control group (the usual method) and the experimental group (Karen model) was in favor of the experimental group. . Among the most prominent conclusions proved the effectiveness of the use of the Karen model in increasing the level of acquisition of second-grade students, the average way of thinking compared to the usual method, and among the proposals for general education directorates to establish courses for male and female teachers of history subject on how to use the Karen model and the application of this model in courses that are prepared for teachers And female teachers. The recommendations are to conduct comparative studies between the effect of the Karen model and other educational models on acquiring historical concepts and for the different academic levels.